Access, Resources, and Classes in the History of Capitalism: A Theory of Social Stratification from a Cognitive Materialist Perspective - Mariano Zukerfeld; Guillermina Yansen (tripleC: Communication, Capitalism & Critique, 2016)
This article aims to apply some concepts from cognitive materialism to the sociological problem of social stratification in capitalism, both in theoretical and abstract terms and through concrete historical examples. After discussing the necessity for a theory of social classes, a division is presented between two types of resources: those intensive in material and energy, and those which are knowledge intensive. At the same time three alternative conditions of access to these resources are theorized: exclusive access (applicable to physical or intellectual property), non-exclusive access, and no access. Combining the different types of resource with the different types of access, we obtain a proposal for a theory of classes (reclaiming this theory as the most powerful for the analysis of social stratification) which we apply, in a simplified and schematic way, to various periods. Thus, we analyze social strata in the transition from feudalism to mercantile capitalism, the subsequent transition to industrial capitalism (in which we distinguish two clearly differentiated stages), and finally, in the current transformation into informational capitalism.